Is Working from Home Here to Stay? A Look at 35 Million Job Ads - Jean-Victor Alipour; Christina Langer; Layla O'Kane (CESifo Forum, 2021)
We analyze the prevalence of working from home (WfH) inGermany using more than 35 million online job advertisements from 2014 to 2021. While a WfH option was rare in jobads before the crisis, the Covid-19 shock led to an unprecedented WfH boom. At the same time, regional, occupational,and sectoral inequalities in access to WfH have decreased during the pandemic. We also document a higher demand for digital skills, teamwork, and adaptability in job ads with a WfH option. We conclude with an outlook for the future of WfH.
Keywords: 330